2020
DOI: 10.1007/s42452-020-03255-3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and recharge effect on spatial changes in the groundwater chemistry of Punjab, Pakistan: a multivariate statistical approach

Abstract: This study presents deterioration in groundwater quality of highly populated region of Punjab Province, Pakistan, by linking chemical data with rain, river recharge, and socioeconomic factors. Various chemical parameters like total dissolved solid (TDS), arsenic (As), fluoride (F − ), Iron (Fe), nitrate (NO 3 − ), nitrite (NO 2 − ), and pH were determined for 46,457 samples collected from 205,344 km 2 area of the Punjab. The samples were collected, stored, and analyzed as per the Environment Protection Agency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…The irrigated area of Multan is very highand salinity is also highest in the province (Figure 2). The Central Punjab is highly polluted followed by Southeast Punjab as reported by Khan and Khan, 2020. The results indicated that salinity and area under wheat has inverse relationship.…”
Section: Resultsmentioning
confidence: 79%
“…The irrigated area of Multan is very highand salinity is also highest in the province (Figure 2). The Central Punjab is highly polluted followed by Southeast Punjab as reported by Khan and Khan, 2020. The results indicated that salinity and area under wheat has inverse relationship.…”
Section: Resultsmentioning
confidence: 79%